The head & neck I, Paranasal sinuses & anterior skull base - Hillen, Berend (Amsterdam: Elsevier Science, 1993)
(Producer) Presents 11,000 images of normal anatomy and 700 correlative images from CT, MRI, and histology. Enables medical professionals to explore interactively the major structures of the nose, paranasal sinuses, orbit, sella turcica, hypophysis, cavernous sinus, and sphenopalatine fossa. All structures are displayed as continuous cross-sectional photographs (taken from the same head) in coronal, sagittal, and axial directions. These images can be displayed as stills or video animation and can be viewed with or without the names of the structures in nomina anatomica. Also includes Mallory-stained histological images in coronal direction from the same head.
CD is available at Koleksi media, Perpustakaan HUKM
Includes one CD-I disc and one CD-ROM
CD-ROM version copyright 1991 by OWL International
System requirements: IBM-compatible PC with a 33 MHz 486 CPU or better (will run on a minimum of 386 CPU, but video playback will be at a lower speed); 4 Mb internal memory, 5 Mb available on hard disk for installation; MS-Windows 3.1; CD-ROM player with adequate access time (less than 400 milliseconds); mouse or other pointing device compatible with MS-Windows; accelerated 256 color VGA adapter compatible with MS-Windows (resolution 640 x 480) (will run on a non-accelerated VGA adapter, but video playback will be at a lower speed)
Keywords: Face -- antomy & histology -- CD-ROM; Paranasal Sinuses -- anatomy & histology -- CD-ROM; Diagnostic Imaging -- CD-ROM